Comparative study and optimal design of alternative PM configuration transverse flux linear machine - Zhu, Shaohong; Cox, Tom; Gerada, C.; Xu, Zeyuan (2017)
This paper presents the comparative study and optimal design of a transverse flux linear machine with different PM configurations, viz. surface-mounted and consequent-pole, in which the consequent-pole version is firstly proposed. Firstly, the effect of variation of the main design parameters on both topologies are studied. Then, the multi-objective optimization method based on genetic algorithm combined with response surface methodology (RSM) is adopted to realize the optimal design of these two topologies and Pareto front solutions will be obtained. Finally, the characteristics of these two topologies are analyzed and compared, with particular regard to the advantages and disadvantages of the consequent pole topology.